The first genome assembly of fungal pathogen Pyrenophora tritici-repentis race 1 isolate using Oxford Nanopore MinION sequencing - Moolhuijzen, Paula; See, Pao Theen; Moffat, Caroline (2021)
Objectives: The assembly of fungal genomes using short-reads is challenged by long repetitive and low GC regions. However, long-read sequencing technologies, such as PacBio and Oxford Nanopore, are able to overcome many problematic regions, thereby providing an opportunity to improve fragmented genome assemblies derived from short reads only. Here, a necrotrophic fungal pathogen Pyrenophora tritici-repentis (Ptr) isolate 134 (Ptr134), which causes tan spot disease on wheat, was sequenced on a MinION using Oxford Nanopore Technologies (ONT), to improve on a previous Illumina short-read genome assembly and provide a more complete genome resource for pan-genomic analyses of Ptr.